Impact Study of Maslamani Photovoltaic System on Tubas Distribution Grid - Alqam, Ahmad; Sobeh, Salam; Awaisah, Nade (جامعة بوليتكنك فلسطين - هندسة طاقة, 2018)
تعاني فلسطين من نقص في مصادر إنتاج الطاقة الخاصة بها، لذلك فهيَ تعتمد بشكل أساسي على الشركات الإسرائيلية, مما يجعل الاحتلال يتحكم في سعر الكهرباء ووقت تشغيلها, ومن هنا جاءت الحاجة لإيجاد مصادر طاقة خاصة بنا, مثل أنظمة الطاقة الشمسية. تعتبر مصادر الطاقة الشمسية من مصادر الطاقة المتجددة الأكثر انتشارا مقارنة بالمصادر الأخرى, ويعود السبب في ذلك لكونها صديقة للبيئة, ومتوفرة بشكل دائم, والكفاءة العالية لهذه الأنظمة. ولحل لمشاكل الطاقة المتفاقمة في بلادنا, توجهنا إلى تنفيذ هذه المشاريع الضخمة وربطها على شبكات التوزيع, ولضمان أعلى كفاءة لمثل هذه الأنظمة, نشأت الحاجة لعمل دراسات لتأثير ربط أنظمة الخلايا الشمسية ذات القدرة العالية على شبكات التوزيع. يقوم هذا المشروع على عمل دراسة تحليلية مفصلة لعملية ربط محطة خلايا شمسية ذات قدرة عالية مع شبكة التوزيع، والحصول على أعلى إنتاجية من النظام, ودراسة الآثار الجانبية الناتجة عن عملية الربط، وإيجاد أفضل الحلول لهذه المشاكل وتطبيقها على الشبكة. نقوم في هذا المشروع على عمل دراسة عن تأثير ربط محطة المسلماني الكائنة في مخيم الفارعة جنوب طوباس والتي قدرتها (3MW) مع شبكة التوزيع، حيث تم الحصول على المعلومات التفصيلية الخاصة بالمشروع من شركة الكهرباء ومن المهندسين القائمين على المشروع، وتم عمل محاكاة للمشروع باستخدام برنامج E-Tap . Abstract Palestine suffers from a lack of sources of its own energy production, so it depends mainly on Israeli companies, which makes the occupation controls the price of electricity and time of operation, hence the need to find our own energy sources, such as solar systems. The sources of solar energy from renewable energy sources are the most widespread compared to other sources. This is because they are environmentally friendly, always available, and the high efficiency of these systems. In order to solve the growing energy problems in our country, we have embarked on implementing these huge projects and connecting them to distribution networks, and to ensure the highest efficiency of such these systems, the need arise for impact studies of connecting high-capacity photovoltaic systems to distribution networks. This project is based on a detailed analytical study of the process of connecting a high-capacity photovoltaic station with the distribution network, and get higher productivity of the system, studying the side effects of the connecting process, and finding the best solutions for these problems and apply these solutions on the network. In this project, we will study the impact of connecting the maslamani station which located in Al-Faraa camp south of Tubas with the distribution network, the detailed information about the project was obtained from the electricity company and the project engineers. The project was simulated using the E-Tap software.
no of pages 92 , CD , هندسة طاقة 4/2018 , in the store
Keywords: Maslamani Photovoltaic System; Distribution Grids